THE INFLUENCE OF GLOBALIZATION PROCESSES ON THE MODERN BANKING SYSTEM OF UKRAINE - Bobil, V. V. (Science and Transport Progress, 2008)
In the article a problem of influence of the foreign capital on the financial market ofUkraineis considered; the positive and negative factors of the globalization processes are investigated. The basic directions of reforming of the domestic bank system in the long-term and intermediate term periods are offered.